The Monetary Roots of Exploitation - Corrado Andini (Institute of Labor Economics (IZA), 2025)
This paper proposes a theory of the mark-up that is embedded in a circuit model of the capitalist mode of production. The model and the theory are built on Keynes's principle of effective demand, Graziani's monetary theory of production and Pivetti's monetary theory of distribution. The price-setting mechanism is conceived as driven by a Kaleckian rule. The rate of interest on bank loans and the propensities to save of different macro-players are shown to affect the level of the mark-up, thus contributing to explain "labour exploitation" as measured by the average gap between worker's pay and productivity. In other words, "labour exploitation" is seen as being in part originated by monetary phenomena, such as the rentability of bank credit and the macro-players' propensities to accumulate money in a bank account.
Keywords: B22; E11; E12; E40; 330; profit; wage; money; finance; capitalism